Transition from Ziprasidone IM to Oral Formulation in Agitated Patients with Acute Exacerbation of Schizophrenia: An Open Trial - Mautone, A.; Scarone, S.; null (Pharmacopsychiatry, 2011)
A transition from IM to oral formulation of an antipsychotic agent is often required during the long-term management of schizophrenia. This multicenter trial evaluates the IM/oral sequential administration of ziprasidone in agitated subjects with an exacerbation of schizophrenia.Adult patients requiring IM therapy for schizophrenic symptoms were assigned to IM ziprasidone 10 mg for 3 days, followed by oral ziprasidone (initial dose: 80 mg/day) for 8 weeks. The primary efficacy outcomes were the change in the total PANSS and in the CGI-S scores vs. baseline values.In total, 150 patients were included in the study. A decline in the PANSS and CGI-S scores was observed throughout the study (p<0.0001 vs. baseline): these reductions became significant at the point of transition from IM to oral formulation (p<0.0001 vs. baseline).Even with the limitations of any non-comparative study, these results suggest that the IM/oral sequential administration of ziprasidone is an effective and well tolerated therapeutic option in the management of acute exacerbations of schizophrenia in agitated patients.
Keywords: acute exacerbation; antipsychotic agents; schizophrenia; transition; ziprasidone